2023
DOI: 10.1149/1945-7111/acaf44
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Redox Shuttle Generated in LFP/Graphite and NMC811/Graphite Cells

Abstract: Unwanted self-discharge of LFP/AG and NMC811/AG cells can be caused by in-situ generation of a redox shuttle molecule after formation at elevated temperature with common alkyl carbonate electrolyte. This study investigates the redox shuttle generation for several electrolyte additives, e.g., vinylene carbonate and lithium difluorophosphate, by measuring the additive reduction onset potential, first cycle inefficiency and gas evolution during formation at temperatures between 25 and 70°C. After formation, elect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
40
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(41 citation statements)
references
References 51 publications
1
40
0
Order By: Relevance
“…Additionally, even within the class of glass fiber separators, there are differences in the SiO 2 content so that two given glass fiber separators might not provide directly comparable cell test results. Recently, it has been found that PET containing tape (here we uses a PET‐based separator) within cells can form redox shuttle molecules, namely DMT, which cause self‐discharge of the cell [35] . This effect, however, can be negated using VC as an additive, which is the case in the present study.…”
Section: Resultsmentioning
confidence: 61%
See 1 more Smart Citation
“…Additionally, even within the class of glass fiber separators, there are differences in the SiO 2 content so that two given glass fiber separators might not provide directly comparable cell test results. Recently, it has been found that PET containing tape (here we uses a PET‐based separator) within cells can form redox shuttle molecules, namely DMT, which cause self‐discharge of the cell [35] . This effect, however, can be negated using VC as an additive, which is the case in the present study.…”
Section: Resultsmentioning
confidence: 61%
“…Recently, it has been found that PET containing tape (here we uses a PETbased separator) within cells can form redox shuttle molecules, namely DMT, which cause self-discharge of the cell. [35] This effect, however, can be negated using VC as an additive, which is the case in the present study. The thickness of the separator and also its porosity and compressibility will directly influence the stack height and thus the cell pressure.…”
Section: Other Considerations For Cell Manufacturingmentioning
confidence: 50%
“…The initial discharge capacities of 2VC cells are mostly unaffected by the formation temperature, due to the better passivation of the negative electrode with VC (⩾165 and ⩾200 mAh for 4.06 and 4.2 V, respectively). 13,15 The reversible losses of the NMC811/AG CTRL cells in Fig. 4 are smaller than those of the LFP/AG cells in Fig.…”
Section: Resultsmentioning
confidence: 91%
“…This is consistent with Buechele et al, who saw lower FCE and thus lower discharge capacity when increasing the formation temperature beyond 40 °C. 15 The initial discharge capacities of 2VC cells also decrease with increasing formation temperature, but not as much as for CTRL cells, since VC contributes to the buildup of a well-passivating SEI, making the influence of formation temperature less apparent. 13 An additional 4.2 V hold after formation does not have a strong influence on the initial capacities (see Fig.…”
Section: Resultsmentioning
confidence: 96%
“…The influence and activity of LiDFP and 2‐SBA as redox shuttle, as reported by Metzger et al., are discussed in the supporting information (Figure S8, Supporting Information). [ 36–38 ] The electrochemical performance of cells containing BE and different concentrations of additives are shown in Figures S3–S6 (Supporting Information).…”
Section: Resultsmentioning
confidence: 99%